Adaptive Management Strategy in Agrucultural Human Resources Development to Support Food Self-Sufficiency - Suarman, Agus; Samuddin, Syurwana Farwita (Economics and Digital Business Review, 2026)
The urgency of this research lies in the critical importance of developing adaptive and innovative agricultural human resources to achieve sustainable food self-sufficiency in Gowa Regency. This study aims to identify and implement effective adaptive management strategies in enhancing farmers’ capacity to become more responsive to the dynamics of modern agriculture. The research employs a qualitative approach, with data collected through interviews, documentation, field observations, and Focus Group Discussions (FGD), which were analyzed using NVivo 12 Plus to identify themes and inter-variable relationships. Data validity was ensured through source and methodological triangulation. The findings of this study indicate that the implementation of adaptive management in agricultural human resource development in Gowa Regency is on the right track to support food self-sufficiency; however, it continues to face a number of constraints at each stage of the process. Needs identification, adaptive planning, and program implementation are underway, yet remain limited in terms of coverage, innovation, and data integration. Monitoring and evaluation are conducted, though not yet optimal due to the limited number of extension workers and inadequate information systems. Strategic adjustments are hampered by bureaucratic processes and budget constraints, while inter-actor collaboration has yet to reach its full potential. Therefore, the effectiveness of adaptive management can only be optimized when reinforced by the integration of information technology, enhancement of extension workers’ capacity, expanded access to training, and more intensive multi-actor synergy